Sound frequency and aural selectivity in sound-contingent visual motion aftereffect. - Maori Kobayashi; Wataru Teramoto; Souta Hidaka; Yoichi Sugita (PLoS ONE, 2012)
BACKGROUND: One possible strategy to evaluate whether signals in different modalities originate from a common external event or object is to form associations between inputs from different senses. This strategy would be quite effective because signals in different modalities from a common external event would then be aligned spatially and temporally. Indeed, it has been demonstrated that after adaptation to visual apparent motion paired with alternating auditory tones, the tones begin to trigger illusory motion perception to a static visual stimulus, where the perceived direction of visual lateral motion depends on the order in which the tones are replayed. The mechanisms underlying this phenomenon remain unclear. One important approach to understanding the mechanisms is to examine whether the effect has some selectivity in auditory processing. However, it has not yet been determined whether this aftereffect can be transferred across sound frequencies and between ears. METHODOLOGY/PRINCIPAL FINDINGS: Two circles placed side by side were presented in alternation, producing apparent motion perception, and each onset was accompanied by a tone burst of a specific and unique frequency. After exposure to this visual apparent motion with tones for a few minutes, the tones became drivers for illusory motion perception. However, the aftereffect was observed only when the adapter and test tones were presented at the same frequency and to the same ear. CONCLUSIONS/SIGNIFICANCE: These findings suggest that the auditory processing underlying the establishment of novel audiovisual associations is selective, potentially but not necessarily indicating that this processing occurs at an early stage.